Empowering Vocational Students: Developing a Culture of Legal Awareness at State Vocational High School 2 Temanggung - Kurniaty, Yulia; Muhammad, Fadil; Santoso, Adi; Astuti, Nanda Widia; Hidayati, Fitria (Borobudur Journal on Legal Services, 2025)
Juvenile delinquency problems, such as brawls, drug abuse, and cybercrime (including cyberbullying and online gambling), often involve Vocational High School (SMK) students, indicating low legal awareness (legal literacy). The purpose of this community service activity is to equip students as law-abiding citizens and understand the consequences of unlawful actions. The method used through interactive counseling and discussion. The material is focused on six crucial issues relevant to adolescents including Narcotics, Liquor, Bullying, Online Gambling, Brawls/Fights, and Legal Aspects of Protests. The results showed high enthusiasm from the participants and confirmation that the issue of Online Gambling and Bullying has high relevance for students. The implementation of the activity succeeded in providing effective educational interventions, as evidenced by the knowledge transfer that occurred. Furthermore, the program for Building a Culture of Legal Awareness has succeeded in instilling the values of legal compliance from an early age and significantly contributes to building a culture of legal awareness in the school environment.